2007
DOI: 10.1016/j.steroids.2007.05.007
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α and glucocorticoid receptor interaction in L6 muscle cells: A cooperative downregulation of myosin heavy chain

Abstract: Sepsis is associated with increased expression of TNF-α with subsequent activation of nuclear factorkappa B (NF-κB). The glucocorticoid receptor (GR) and NF-κB function as mutual antagonists and induction of the latter is believed to play a major role in the acquired glucocorticoid resistance that occurs in some septic patients. GR expression and function has been reported to be elevated in septic muscle suggesting a limited effect of the activated NF-κB on GR function in this context. In this study, the L6 my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 38 publications
(43 reference statements)
2
26
0
Order By: Relevance
“…It has been reported that GR expression is downregulated in L6 myocyte cells when treated with the synthetic glucocorticoid, DEX (Dekelbab et al, 2007). Consistent with this, Figure 4.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…It has been reported that GR expression is downregulated in L6 myocyte cells when treated with the synthetic glucocorticoid, DEX (Dekelbab et al, 2007). Consistent with this, Figure 4.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, GR expression also increases in L6 skeletal muscle cells in vitro when treated with serum from septic rats. However, downregulation of GR was observed in cells cultured in the resting state (Dekelbab et al, 2007). The findings above suggest that GC levels rise in the body during sepsis, but GC resistance appears in inflammatory cells, thus anti-inflammatory factor GC does not suppress the excessive inflammatory response.…”
Section: Introductionmentioning
confidence: 82%
“…Collectively, our data support the idea that GILZ/L-GILZ could be targets for future therapies of myopathies and for control of GC-mediated antimyogenic effects. Indeed, GC treatment has been reported to result in reduced myogenesis and inhibition of the activation of muscle satellite cells (7,8). These observations might call for a reconsideration of anti-inflammatory GC therapy of myopathies as well for new therapeutic strategies aimed to counter GC side effects at the muscle tissue level.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, GC effects on differentiating myoblasts have not been extensively investigated. In fact, despite the evidence that dexamethasone (DEX) treatment results in reduced myogenesis and inhibition of the activation of the adult stem cells in skeletal muscle tissue known as satellite cells (7,8), the molecular determinants of these biological effects are still poorly understood.…”
mentioning
confidence: 99%
“…1). In mammals, the rat L6 myoblastic cell line expresses MHC in both growth and differentiation media (Dekelbab et al 2007). In contrast, mouse C2C12 myoblasts do not express MHC in growth medium, but they do express it in differentiation medium (Artaza et al 2002).…”
Section: Discussionmentioning
confidence: 99%